Optimization of standard arrival procedures at Sheremetyevo airport using rnav path terminators - G. A. Gasparyan; M. V. Kulakov (Научный вестник МГТУ ГА)
Holding patterns are established at international airports to make the arriving traffic flow smooth and efficient. One of the main aims of holding patterns is to extend the aircraft arrival route, which allows ATC units to arrange the sequence on the arrival routes more effectively. The article considers the current methods and offers new ideas to improve the efficiency of the inbound traffic flow management using Paths and Terminators concept with HA holding patterns for standard arrival routes at Sheremetyevo Airport. As the main idea for optimizing air traffic management on this stage and reducing the workload on the controller, it is proposed to create extra routes in addition to the existing ones which include holding patterns, that will be used when needed to ensure a well-ordered traffic. The probabilistic method is used to calculate the maximum capacity of existing and proposed arrival routes with holding patterns. The proposed options for restructuring the airspace of the Moscow Terminal Control Area with preserving waypoints of starting standard arrival routes are presented.